Empowering Women's Coconut Farmer Groups To Build Family Economic Resilience Based On Local Potential In Tidore Islands City - Zubair Saing; Haryati La Kamisi; Hamidah Rahman; Similanti Udin; Safira Safira; Dewi Titdoy; Elfhy Yanti Karim (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Coconut farmers' homes may have a poor economy or income since their goods rely solely on one primary commodity: copra and coconut grains. It can potentially upset economic circumstances since, as the price of copra and coconut falls, so does household income. As a result, help for coconut farmers, notably women farmer organizations, is required to boost the economic worth of their coconuts. For example, the economic value of coconut may be improved by producing various coconut-based goods so that farmers are not only reliant on copra prices. According to the survey findings and the identification of problems with the partners of the women's group Tani Igo Jaya, based in Jaya Village, Tidore Islands City, all members have encountered economic difficulties due to the drop-in copra prices. It was exacerbated by the fact that it occurred concurrently with the COVID-19 epidemic. As a result, most coconut growers refuse to process their coconuts into copra, and some coconuts go to waste. The issue is that partners lack expertise and abilities in processing or diversifying processed coconuts, although all components of the coconut fruit may be utilized to generate economic value. The solution that will be applied to partners is the transfer of science, technology, and skills for partners in processing their coconut harvests, as well as the provision of solid business management so that partners are not only reliant on copra. Furthermore, the identification of waste concerns from processed coconut fruit will be minimized since partners can employ coconut water, coconut pulp, and coconut fiber, which are presently considered waste but have promising economic value. This community service project is intended to create a new entrepreneurial group by exploiting possible sources of local raw materials available to partners, and it will directly benefit the economic resilience of coconut growers' homes. This community empowerment activity was successful in increasing partners' knowledge and skills in processing coconut fruit into nine products: coconut confectionery, shredded coconut (serundeng), coconut chips, sweet soy sauce, coconut jam, coconut milk, coconut oil, virgin coconut oil (VCO), and pots, as well as planting media made from coconut coir.